KRITIK JÜRGEN HABERMAS TERHADAP PERAN DAN FUNGSI AGAMA DALAM MASYARAKAT MODERN - Bhanu Viktorahadi (Jurnal Theologia, 2017)
Abstract: The wrong understanding of role and function of religion will make religion just function as instruments of legitimating those who use it irresponsibly. Therefore, it is important to take a certain paradigm to see and analyze the role and function of religion. That paradigm in its turn will restore religion in its essential role and function as a system of orientation and interpretation of the meaning of human life, as well as its relationship with God and others. The Theory of Religious Criticism and Communicative Practical Theory of Jürgen Habermas offers evaluative, reflective, and corrective critics of the role and function of religion. The fired criticism will, in turn, help religion restore its role and function as a bridge communicative and relational between human and God and the others. At the same time, religion is expected to return to its role and function in contributing to the realization of a receptive society in rational discursive rooms which in turn will enable the process of human emancipation. The further process of human emancipation is the formation of an increasingly strong personal and social identity, rooted in values or virtues derived from religion itself as the bridge that leads people to the real truth.Abstrak: Pemahaman peran dan fungsi agama yang keliru akan menjadikan agama sekadar menjadi alat legitimasi pihak yang memanfaatkannya secara tidak bertanggung jawab. Oleh karena itu, dibutuhkan paradigma untuk melihat sekaligus menganalisis peran dan fungsi agama supaya kembali pada hakikatnya sebagai sistem orientasi dan interpretasi atas hidup manusia pemaknaannya, serta relasinya dengan Tuhan dan sesama. Teori Kritik Agama dan Teori Praksis Komunikatif dari Jürgen Habermas menawarkan peluru-peluru kritik evaluatif, reflektif, dan korektif atas peran dan fungsi agama. Kritik yang ditembakkan tersebut pada gilirannya akan membantu agama mengembalikan peran dan fungsinya sebagai jembatan penghubung antara manusia dengan Tuhan dan sesamanya yang bersifat komunikatif dan relasional. Sekaligus dengan itu, agama diharapkan kembali pada peran dan fungsinya dalam memberi sumbangan atau berkontribusi pada upaya mewujudkan masyarakat yang reseptif pada ruang-ruang diskursif rasional yang pada gilirannya akan memungkinkan proses emansipasi kemanusiaan. Proses selanjutnya dari emansipasi kemanusiaan adalah pembentukan identitas personal dan sosial yang semakin kuat, yang berakar pada nilai-nilai atau keutamaan yang berasal dari agama itu sendiri sebagai jembatan yang mengarahkan manusia kepada kebenaran sejati.